Determinants of bank’s efficiency during financial liberalization in Malaysia / Nur Zahidah Bahrudin - Bahrudin, Nur Zahidah (Institute of Graduate Studies, UiTM, 2016)
Financial institutions have been found to be one of the major contributors to the economy of numerous countries. The failure of this industry can affect the economic growth and the expanding economic opportunity. In the globalization landscape, financial liberalization also takes place, in which, the central bank permits foreign bank ownerships to invest and to establish their plans locally. The existence of foreign banks has created competitions for local owned banks when they attempt to achieve full efficient performance, as well as in becoming leaders in the market. In addition, the Malaysian government has implemented the new policy named Financial Sector Master Plan (FSMP) in order to strengthen and enhance the local banks operation. Therefore, the assessment of whether local banks have outperformed foreign banks is crucial, especially due to the execution of FSMP for the Malaysian banking system. For that reason, this study examined cost, revenue, and profit efficiency of both local and foreign banks in Malaysia. As the banking system has experienced major changes as a result of the program implemented by the central bank to improve the Malaysian banking sector, the analysis of this study was divided into three time range periods, which were: i) during the Asian financial crisis, ii) before the implementation of FSMP, and iii) since the inception of FSMP program…